Jane and the twelve days of Christmas : being a Jane Austen mystery - Barron, Stephanie (Barron, Stephanie. Jane Austen mystery., 2014)
"The twelfth installment in Stephanie Barron's fan-favorite Being a Jane Austen Mystery series. Christmas Eve, 1814: Jane Austen has been invited to spend the holiday with family and friends at The Vyne, the gorgeous ancestral home of the wealthy and politically prominent Chute family. As the year fades and friends begin to gather beneath the mistletoe for the twelve days of Christmas festivities, Jane and her circle are in a celebratory mood: Mansfield Park is selling nicely; Napoleon has been banished to Elba; British forces have seized Washington, DC; and on Christmas Eve, John Quincy Adams signs the Treaty of Ghent, which will end a war nobody in England really wanted. Jane, however, discovers holiday cheer is fleeting. One of the Yuletide revelers dies in a tragic accident, which Jane immediately views with suspicion. If the accident was in fact murder, the killer is one of Jane's fellow snow-bound guests. With clues scattered amidst cleverly crafted charades, dark secrets coming to light during parlor games, and old friendships returning to haunt the Christmas parties, whom can Jane trust to help her discover the truth and stop the killer from striking again?"--